A brief history of tuberculosis in the Czech Lands. (July 2017) - Vargová, Lenka; Vymazalová, Kateřina; Horáčková, Ladislava
Abstract: Tuberculosis currently remains a serious medical problem, therefore increased attention is being paid to this disease. Paleopathological studies focused on the monitoring of morbid changes in skeletal remains of historical populations facilitate a detailed study of the development of this disease. They provide direct evidence of the existence of tuberculosis and its past forms. In addition to literary and iconographic sources, the present study is focused on recording the findings of bone tuberculosis in historical osteological sets from the Czech Lands and is the starting point for their detailed review. Approximately 76 cases of bone tuberculosis from the Czech Lands have been published and more or less reliably documented from 20 archeological sites dated back from the Eneolithic to the modern period.